2022
DOI: 10.1007/s10584-022-03394-z
|View full text |Cite
|
Sign up to set email alerts
|

Climate adaptation in the market squid fishery: fishermen responses to past variability associated with El Niño Southern Oscillation cycles inform our understanding of adaptive capacity in the face of future climate change

Abstract: Evaluating the strategies fishermen have used to respond to short-term climate variability in the past can help inform our understanding of the adaptive capacity of a fishery in the face of anticipated future change. Using historic fishery landings, climate records, and fishermen surveys, we document how market squid fishermen respond to high seasonal and interannual climate variability associated with the El Niño Southern Oscillation (ENSO) and responses to hypothetical future scenarios of low abundance and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Operators might have temporarily or permanently relocated their tours to other reef sites that were of similar quality to the sites they were using before the disturbance, and thus visitor experiences might have been comparable before and after. Our findings align with other recent empirical studies that identified spatial diversification as key adaptation strategy to environmental change (Pecl et al 2019 ; Silas et al 2020 ; Gonzalez-Mon et al 2021 ; Powell et al 2022 ) and as an important response by alpine tourism operators affected by climate change (Hoffmann et al 2009 ; Mourey et al 2020 ; Welling and Abegg 2021 ). In our cyclone-impacts sample, about 80% of operators responded by changing their reef sites.…”
Section: Discussionsupporting
confidence: 91%
“…Operators might have temporarily or permanently relocated their tours to other reef sites that were of similar quality to the sites they were using before the disturbance, and thus visitor experiences might have been comparable before and after. Our findings align with other recent empirical studies that identified spatial diversification as key adaptation strategy to environmental change (Pecl et al 2019 ; Silas et al 2020 ; Gonzalez-Mon et al 2021 ; Powell et al 2022 ) and as an important response by alpine tourism operators affected by climate change (Hoffmann et al 2009 ; Mourey et al 2020 ; Welling and Abegg 2021 ). In our cyclone-impacts sample, about 80% of operators responded by changing their reef sites.…”
Section: Discussionsupporting
confidence: 91%
“…In order to prevent excessive fishing effort (facilitated by newer, larger, and more efficient vessels) and allow for critical periods of uninterrupted spawning, the CDFW developed the Market Squid FMP in 2005, which consists of several static management measures including: a fixed seasonal catch limit of 118,000 tons, 2-day weekend closures, light and gear restrictions, a restricted access program, and monitoring programs (port sampling and logbooks) (CDFW, 2005). Market squid populations, and associated catch, fluctuate dramatically in response to variations in ocean conditions, declining drastically in unfavorable environments associated with El Niño events, characterized by warm SST and low productivity, and rebound rapidly during favorable conditions associated with La Niña events, characterized by cool SST and high productivity (Reiss et al, 2004;van Noord and Dorval, 2017;Powell et al, 2022).…”
Section: Study Fisheriesmentioning
confidence: 99%
“…Squid fishermen historically have shifted effort among coastal pelagic finfish species (i.e., Pacific sardine, Pacific and jack mackerel, and northern anchovy) in response to fluctuations in resource availability or demand associated with climate, market, and regulatory changes (Pomeroy et al, 2002;Aguilera et al, 2015). Coastal pelagic finfish permits are the most frequently held additional permit for market squid fishermen (Powell et al, 2022) due to their overlapping ranges, and overlapping requirements for gear, vessels, and personnel (Pomeroy et al, 2002). Despite the interconnectedness of these fisheries and the flexibility it historically afforded fishermen, recent closures of the sardine fishery, an overall decrease in market value, and quota reductions now undercut the advantages of having this permit, meaning the most complementary and commonly held additional permit no longer increases flexibility (Powell et al, 2022).…”
Section: Regulatory Constraintsmentioning
confidence: 99%
See 2 more Smart Citations